Virulence and phylogenetic analysis of enteric pathogenic Escherichia coli isolated from children with diarrhoea in South Africa - Ntando W. Alfinete; John Y. Bolukaoto; Lee Heine; Natasha Potgieter; Tobias G. Barnard (International Journal of Infectious Diseases, 2022)
ABSTRACT: Background: : Diarrhoeagenic Escherichia coli pose a significant risk to human health. As such, determining the source(s) of these bacteria when isolated from patients with diarrhoea is an important step in disease prevention. Objectives: : To identify the presence of genes coding for virulence and phylogroups among E. coli isolated from children hospitalized due to diarrhoea in Limpopo Province, South Africa. Methods: : E. coli isolates were identified using the VITEK-2 automated system. An 11-gene multiplex polymerase chain reaction (PCR) was used to differentiate five pathogenic types of E. coli: enteroaggregative (EAEC), enteroinvasive (EIEC), enterohaemorrhagic (EHEC), enteropathogenic (EPEC) and enterotoxigenic (ETEC). The Clermont quadruplex PCR method was used to identify phylogroups of isolates. Results: : From the 133 isolates tested, 79 were confirmed as E. coli. Of these, 19.0% (15/79) were commensals and 81.0% (64/79) were positive for at least one pathotype, of which ETEC was predominant (16.5%, 13/79), followed by EAEC (10.1%, 8/79), EPEC (7.6%, 6/79) and EHEC (2.5%, 2/79). Hybrid pathotypes were also detected and EAEC/ETEC was predominant (25.3%, 20/79). Phylogroup B2 was predominant (30.4%, 24/79), followed by phylogroup B1 (22.8%, 18/79), and phylogroups C and E (both 12.7%, 10/79). Just over 6% (5/79) of isolates were non-typable. Conclusion: : There was a high distribution of diarrhoeagenic E. coli associated with different phylogroups among children living in Limpopo Province, South Africa. This emphasizes the importance of future monitoring of virulence and phylogroup distribution of E. coli isolates in this province in particular and in South Africa as a whole.